Connectors, electrical, circular, coupled by threaded ring, fire-resistant or non fire-resistant, operating temperatures 175°C continuous, 200°C continuous, 260°C peak. Plug. Product standard Part 8, (15th September 1997) - British Standards Institution,
No abstract available